PREPARASI DAN KARAKTERISASI NANOPARTIKEL Fe3O4 MENGGUNAKAN METODE KOPRESIPITASI - Ani Santi Lestari; Dewi Sartika (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2018)
Nanoparticles is a material or particle which nanometers size. It has done research making nanoparticles Fe3O4 with kopresipitation methods then characterization XRD and TEM to knowing the characteristic and particles size of sample. The result of characterization XRD detected by appearing the peaks difraction an angle of 30; 35,4; 43; 53,4; 56,9; and 62,5. The result of TEM characterization is 13,68 nm and 14,33 nm of particles size.